Answer:
see explanation
Explanation:
A
the equation of a quadratic in vertex form is
y = a(x - h)² + k
where (h, k ) are the coordinates of the vertex and a is a multiplier
here (h, k ) = (1, - 4 ) , then
y = a(x - 1)² - 4
to find a substitute the coordinates of any other point on the graph into the equation.
using (0, - 3 )
- 3 = a(0 - 1)² - 4 ( add 4 to both sides )
1 = a(- 1)² = a ⇒ a = 1
y = (x - 1)² - 4 ← in vertex form
B
the equation of a quadratic in standard form is
y = ax² + bx + c ( a ≠ 0 )
using the result from A
y = (x - 1)² - 4 ← expand the factor using FOIL
= x² - 2x + 1 - 4
y = x² - 2x - 3 ← in standard form